Marketing Strategy and the Potency of Inclusive Education Throughout Surakarta Ex-Residency - Muktiyo, Widodo (Komunitas, 2016)
This research studied marketing strategy and promotion communication in child growth and development clinic as the pillar of inclusive education. Particularly, the objectives of current research were to map the market of child growth and development clinic throughout Surakarta Ex-residency, to recommend the marketing strategy in child growth and development clinic, to analyze the external factors affecting the child growth and development clinic sustainability, and to recommend differentiation and promotion communication of child growth and development clinic. This study was taken place in Surakarta ex-residency. The type of research used was mixed-method. The strategy employed was quantitative descriptive and grounded research. The result of research showed that potency of inclusive education market in Surakarta ex-residency was sufficiently high, as could be seen from the highly potential development of child growth and development clinic. The result of research also showed the marketing strategy of growth and development clinic and market share in each area of Surakarta ex-residency (Solo, Wonogiri, Sukoharjo, Boyolali, Klaten, Sragen): (a) affordable price, (b) product variation adjusted with the most case: learning retarded, mental retarded, quadriplegic, deaf and multiple disabled, (c) safe, kids-friendly physical environment and adequate facility, (d) service hour and time clarity for each type of service, (e) experience medical personnel, (f) promotion  through a variety of media types, (g) cooperation and network system.